Kewarganegaraan sebagai Instrumen Hukum dalam Sengketa Agraria Transnasional - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Hamim sirojuddin Al Manshur; Annisa Sandy Hudha; Suci Ariyanti (Pemuliaan Keadilan, 2025)
This study aims to analyze the role of citizenship as a legal instrument in the resolution of transnational agrarian disputes, which often involve more than one country and raise complex legal issues. The study focuses on three countries, namely Indonesia, Brazil and South Africa, to understand how citizenship affects land ownership and dispute resolution mechanisms. The research method used is a qualitative approach, with interviews, secondary data analysis, and legal policy evaluation. The results show that citizenship plays an important role in determining land rights and influencing the course of dispute resolution. In this context, alignment of national legal frameworks with international legal standards, as well as increased cooperation between countries, is necessary to create more effective and equitable transnational agrarian dispute resolution. This research provides novelty in identifying the importance of legal harmonization and international collaboration in addressing transnational disputes.